Tax neutrality and social justice as principles of taxation in Ukraine - O.Y.; O.V. (Економіка, управління та адміністрування)
Tax relations are a historical permanent and mandatory institution, the nature of which reflects the political, economic, and social aspects of the historical period of development of society, states, and continents. The complexity of such relations led more than once to military, social, economic, and political crises, which affected the justification of the basic principles of working with taxes and the functioning of tax systems. The formation of tax systems of individual countries takes place gradually through the formation and maintenance of tax trust between all subjects of tax relations. Practical assurance of trust in the field of taxation is carried out through the elements of the legal mechanism of taxes and the corresponding principles of taxation, which have undergone changes over the past centuries. The principles of taxation, which ensure the functioning of the taxation system in Ukraine, have changed twice since 1991 – with the adoption of the Law «On the Taxation System in Ukraine» and the Tax Code. The significance of the principles has been studied by scholars for a long time, and among the main ones, neutrality of taxation and social justice, which are applied to individuals and legal entities, should be singled out.